OPTIMALISASI PENINGKATAN PEGAWAI SEKRETARIAT DPRD KABUPATEN CIREBON - Yanto Heriyanto (Jurnal Ilmiah Publika, 2017)
ABSTRACT Title of writing in research Optimization of Staff Enhancement Secretariat DPRD Cirebon. This research is a descriptive research type using qualitative research method. This research is based on the existence of a phenomenon where still found some obstacles in the Optimization of Staff Enhancement Secretariat DPRD Kabupaten Cirebon  Mangkunegara states that in general the performance is divided into two, namely individual performance and organizational performance, individual performance is the work of employees both in terms of quality and quantity based on work standards that have been determined, while organizational performance is a combination of individual performance with group performance (Mangkunegara , 2005).  Problems in research in Performance of staff Secretariat DPRD Kab. Cirebon is an element of service to the Regional House of Representatives. The DPRD Secretariat is headed directly by a Secretary of the DPRD who is technically operational under and directly responsible to the Chairman or Speaker of the DPRD, and is Administratively accountable to the Regent through the Regional Secretary. As stated in Article 20 Paragraph (1) of the 1945 Constitution, the Regional People's Legislative Assembly has duties consisting of the functions of legislation, supervisory function and budget function, therefore the service must be able to accommodate all the basic functions of the Regional People's Legislative Assembly of Kab. Cirebon with a way of achieving good performance by the Secretariat DPRD Kab. Cirebon so that the services provided can give a significant impact on the fulfillment of the people's mandate through the implementation of duties and functions of the DPRD of Cirebon But at the Secretariat of Parliament Cirebon Regency we found some problems that cause not yet Optimal Employee Performance are: Job Performance: Work Achievement is defined as the work achieved by an employee in performing his duties in accordance with the responsibilities given to him in quality of work, Expertise: Expertise is the level of technical ability possessed by employees in carrying out tasks assigned to him, Behavior: Behavior is an attitude and employee behavior attached to him and carried in carrying out his duties